Audio-Visual Speech Intelligibility Benefits with Bilateral Cochlear Implants when Talker Location Varies - van Hoesel, Richard J. M. (J Assoc Res Otolaryngol, 2015)
One of the key benefits of using cochlear implants (CIs) in both ears rather than just one is improved localization. It is likely that in complex listening scenes, improved localization allows bilateral CI users to orient toward talkers to improve signal-to-noise ratios and gain access to visual cues, but to date, that conjecture has not been tested. To obtain an objective measure of that benefit, seven bilateral CI users were assessed for both auditory-only and audio-visual speech intelligibility in noise using a novel dynamic spatial audio-visual test paradigm. For each trial conducted in spatially distributed noise, first, an auditory-only cueing phrase that was spoken by one of four talkers was selected and presented from one of four locations. Shortly afterward, a target sentence was presented that was either audio-visual or, in another test configuration, audio-only and was spoken by the same talker and from the same location as the cueing phrase. During the target presentation, visual distractors were added at other spatial locations. Results showed that in terms of speech reception thresholds (SRTs), the average improvement for bilateral listening over the better performing ear alone was 9 dB for the audio-visual mode, and 3 dB for audition-alone. Comparison of bilateral performance for audio-visual and audition-alone showed that inclusion of visual cues led to an average SRT improvement of 5 dB. For unilateral device use, no such benefit arose, presumably due to the greatly reduced ability to localize the target talker to acquire visual information. The bilateral CI speech intelligibility advantage over the better ear in the present study is much larger than that previously reported for static talker locations and indicates greater everyday speech benefits and improved cost-benefit than estimated to date.